Evaluation of pocket gopher diet in a perennial productive area - Rueda-Torres, Juan Rolando; Gatica-Colima, Ana Bertha; Vital-Garcia, Cuauhcihuatl (THERYA, 2022)
The desert pocket gopher (Geomys arenarius) is a fossorial herbivorous rodent of the family Geomyidae. Its distribution range is restricted to New Mexico and Texas, in the United States of America, and northern Chihuahua, in México. The Médanos de Samalayuca Flora and Fauna Protection Area (MSFFPA) is located in northern Chihuahua. Different economic activities are carried out in this region, mainly irrigated crops of pecans (Carya illinoinensis). Populations of G. arenarius have been recorded within these areas. Therefore, the objective of this work was to define the extent of the trophic niche and the changes in the physical condition of G. arenarius in a ranch within the MSFFPA over three contrasting seasons (dry, wet, and post-wet). Forty G. arenarius specimens were collected from Arantxa Ranch. Morphometric measurements and the weight of collected individuals were recorded, and the digestive tract was removed to prepare histological slides. Seven 25 mÂ²-quadrants were established, and the species of the vegetation cover were recorded and collected for reference. The Seasonal Fitness Index (IK) and Levinâ€™s Niche Breadth Index were calculated. Males had higher average measurements and weight than females. The IK was 2.82 Â± 0.47 in males and 2.64 Â± 0.61 in females. Significant differences in the IK between seasons were only found in females. The correlation between IK and plant cover was strong for males and females. The diet mainly comprised Physalis hederifolia, Dimorphocarpa wislizeni, and Cenchrus incertus. Levinâ€™s index showed that G. arenarius is a specialist rodent. Sexual dimorphism was evident, with males larger than females. The physical condition index of gophers is influenced by resource availability. In other studies, this parameter has been related to changes in food availability. It has been reported that gophers tend to feed mainly on crops; however, pecan cultivation was not a major element in the diet of the desert pocket gopher, as it feeds on the vegetation associated with crops. Gophers are considered generalists; nonetheless, the present study showed that G. arenarius is a specialist, although this may be a consequence of anthropogenic activities.